Magnesium air battery negative electrode component design and preparation method based on free energy adsorption
The free energy of magnesium surface adsorption is calculated through density functional theory and the negative electrode composition of magnesium alloy is designed in combination with the microalloyization strategy, which solves the problems of fast self-corrosion and poor activity of magnesium air batteries, and achieves the improvement of negative electrode efficiency and discharge voltage.
Patent Information
- Application Number
- CN202411899691.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
Magnesium air batteries face the problems of fast self-corrosion of discharge and poor discharge activity, resulting in low efficiency of converting chemical energy into electrical energy and short battery life.
Through density functional theory, the adsorption free energy of different atoms on the surface of magnesium solid solution is calculated, combined with the microalloyization strategy, the components of the magnesium alloy negative electrode are designed, and specific preparation methods are adopted to improve the negative electrode efficiency and discharge voltage.
The negative electrode efficiency of magnesium air battery and the optimization of discharge voltage are achieved, extending the service life of the battery and improving the energy density.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to the field of magnesium-air batteries, and in particular to a composition design method, a preparation method and an application of a negative electrode material for a magnesium-air battery. Background Art
[0002] Metal-air batteries have the advantages of high energy density, stable performance and simple structure, and have attracted much attention. Among typical metal-air batteries, magnesium-air batteries (600-1300W h kg -1 ) and lithium-air batteries (500-1000W h kg -1 ) has a significantly higher energy density than zinc-air batteries (300-500W h kg -1 ), aluminum-air battery (300-500W h kg -1 ) and iron-air batteries (50-75Wh kg -1 ) energy density. Compared with lithium-air batteries, magnesium-air batteries have cost advantages, and my country has abundant magnesium ore resources. The high energy density and low cost make magnesium-air batteries applicable to transportation, communication electronics and other fields, and have broad development prospects.
[0003] However, magnesium-air batteries face the problem of fast self-corrosion during discharge and poor discharge activity, which greatly hinders the further expansion of the application range of magnesium-air batteries. The reasons for the rapid self-corrosion of the magnesium negative electrode during discharge are: the formation of micro-galvanic cells between the magnesium matrix and the second phase, the physical detachment of the magnesium matrix and the second phase (block effect), and the negative difference effect during discharge. The rapid self-corrosion leads to low efficiency in converting the chemical energy of the magnesium negative electrode into electrical energy, and the battery has a short service life. In addition, the surface of the magnesium negative electrode undergoes a dynamic film-forming process of dissolution and re-deposition during discharge, which reduces the electrode reaction sites on the magnesium surface and reduces the actual discharge voltage.
[0004] Alloying is a common method to improve the negative electrode efficiency and discharge voltage of magnesium negative electrodes. However, the traditional "trial and error method" to design alloy composition has problems such as low efficiency and time consumption, resulting in the current negative electrode materials that can simultaneously improve the negative electrode efficiency and discharge voltage are still very limited. Therefore, new magnesium negative electrode material design methods and preparation methods are urgently needed to simultaneously improve the low efficiency and poor discharge activity of magnesium battery negative electrodes. Summary of the invention
[0005] The primary purpose of the present invention is to provide a method for designing negative electrode materials for magnesium-air batteries, that is, to calculate the adsorption free energy of different atoms after solid solution on the magnesium surface by density functional theory, and then design the composition of the magnesium alloy negative electrode based on the adsorption free energy combined with the microalloying strategy; at the same time, a method for preparing negative electrode materials for magnesium-air batteries is provided to simultaneously improve the negative electrode efficiency and discharge voltage of magnesium-air.
[0006] The composition design and preparation method of the magnesium negative electrode material based on adsorption free energy provided by the present invention comprises the following steps:
[0007] (1) Modeling: Using the hexagonal close-packed crystal structure of pure Mg, the 0001 plane was cut out to construct a 4×4×6 supercell of 96 atoms, in which one atom in the surface layer was replaced by a solute atom. The solute atom was another metal element doped in the magnesium alloy. A model doped with different types of solute atoms was constructed to study the effect of the solute atom type on the hydrogen evolution reaction on the magnesium surface at an equal atomic ratio, thereby screening out the appropriate solute element type;
[0008] (2) Structural optimization: Based on step (1), the open source Quantum-ESPRESSO was used for density functional theory calculations, using the Perdew–Burke–Ernzerhof (PBE) exchange-correlation approximation and ultrasoft pseudopotentials with an energy cutoff of 450 eV or 769 eV. The k-point grid was set to 4 × 4 × 1 and the The vacuum layer is used to avoid the mutual influence between periodic units, and the force convergence criterion for atomic structure optimization is 0.01. The total energy convergence criterion is 1×10 -4 eV, the structure was optimized to obtain the stable structures of different doping models and their corresponding energies; in addition, based on the above stable structures, H and H 2 O molecules are placed above the solute atoms, and the same structural optimization method is used to obtain different doping models to stably adsorb H and H 2 The structure of the O molecule and its corresponding energy;
[0009] (3) Calculate the total energy change (ΔE) before and after adsorption: After the structural optimization in step (2), extract the adsorption of H or H by different doping models in the output file. 2 The energy before and after O is the difference between the two and the corresponding isolated H or H is subtracted 2 The energy corresponding to O is obtained to obtain the ΔE corresponding to different doping models. The calculation formula is as follows:
[0010] △E=E 后 -E 前 -E 吸附
[0011] Where ΔE is the adsorption of H or H 2 The total energy changes before and after O, E before and E after are the doping model adsorbing H or H 2 The energy before and after O, E 吸附 Is isolated H or H 2 The energy of O molecules is -1.73eV and -14.22eV respectively;
[0012] (4) Calculation of zero-point energy change (ΔZPE) before and after adsorption: After the structure is optimized in step (2), the adsorption of H or H by different doping models is obtained. 2 O, perform phonon calculations, and extract H or H adsorbed on the surface of different doping models from the output files of phonon calculations. 2 The corresponding vibration frequency after O is calculated by the following formula to obtain the zero-point energy change:
[0013] △ZPE=1 / 2∑hν i -ZPE 吸附
[0014] Where h is Planck's constant, v i The different doping models are H or H adsorbed on the surface 2 The i-th vibration frequency corresponding to O, ZPE 吸附 Is isolated H or H 2 The zero-point energy of O is 0.135 eV and 0.28 eV respectively;
[0015] (5) Calculation of the product of vibrational entropy and temperature (TΔS) before and after adsorption: adsorption of H or H by different doping models 2 After O, the product of the surface vibration entropy and temperature is calculated as follows:
[0016]
[0017] Where T is the temperature, ΔS is the change in vibration entropy before and after adsorption, k B is the Boltzmann constant, h is the Planck constant, and vi is the adsorption of H or H on the surface of different doping models. 2 The i-th vibration frequency corresponding to O, S 吸附 Is isolated H or H 2 The entropy of O;
[0018] (6) Calculation of adsorption free energy (ΔG): After obtaining ΔE, ΔZPE, and TΔS corresponding to different doping models in steps (3) to (5), the surface H or H of different doping models is calculated by the following formula: 2 Adsorption free energy of O:
[0019] △G=△E+△ZPE-T△S
[0020] Where ΔG is the surface H or H 2 O adsorption free energy, ΔE is the adsorption free energy of H or H 2 O is the total energy change before and after, ΔZPE is the change in zero-point energy before and after surface adsorption, and TΔS is the product of the entropy change before and after surface adsorption and the temperature (T is generally set to 300K).
[0021] (7) Composition design: H and H2 The larger the absolute value of either of the two O adsorption free energies, the more favorable it is to inhibit hydrogen evolution, thereby improving the efficiency and initial discharge voltage of the magnesium alloy negative electrode. 2 O adsorption free energy, and compare the absolute values to screen out two doping solute elements. The models corresponding to these two doping solute elements have relatively high H or H 2 The absolute value of O adsorption free energy, the two doped solute elements screened out together with pure magnesium form a ternary magnesium alloy.
[0022] In addition, microalloying is beneficial to suppress the physical shedding effect of the magnesium negative electrode during discharge, thereby improving the negative electrode efficiency. Therefore, the addition amount of the two solute elements generally selected is about 0.5wt.%, and the rest is pure magnesium.
[0023] (8) Preparation: According to the composition obtained in step (7), pure magnesium is preheated and melted in a resistance furnace. After the magnesium is completely melted, the preheated pure metals or intermediate alloys corresponding to the other two elements are added at the same time. During the heating process, ventilation protection (SF 6 +N 2 , gas volume ratio 1:19); after the alloy melt temperature reaches 720°C, it is poured into a metal mold to obtain an ingot.
[0024] application
[0025] The magnesium alloy designed and prepared by the present invention can be used as the negative electrode material of the magnesium-air battery, and can effectively improve the discharge efficiency and discharge voltage of the battery in the traditional aqueous electrolyte, thereby improving the battery energy density. Advantages of the invention:
[0026] 1. Fast composition design: Compared with the traditional "trial and error method", this method can accelerate the design speed of magnesium negative electrode materials.
[0027] 2. Improve the utilization rate of the negative electrode: The alloy reduces the consumption of negative electrode materials during the discharge process, and improves the utilization efficiency and discharge capacity of the negative electrode.
[0028] 3. Optimize discharge voltage: The alloy maintains a stable discharge voltage during discharge, which can meet the needs of efficient energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a microstructure diagram of the negative electrode Mg-0.5Mn-0.5Sn of the magnesium air battery of the present invention.
[0030] Figure 2 The present invention shows the morphology of the negative electrode Mg-0.5Mn-0.5Sn of the magnesium-air battery after discharge and the cross-sectional morphology of the discharge product.
[0031] Figure 3 The electrochemical polarization curve and discharge curve of the negative electrode Mg-0.5Mn-0.5Sn of the magnesium air battery of the present invention are shown. DETAILED DESCRIPTION
[0032] In order to further illustrate the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It is pointed out that these embodiments are only used to illustrate the present invention, rather than to limit the scope of rights of the present invention.
[0033] Example 1
[0034] Material design and preparation
[0035] 1. Using the hexagonal close-packed crystal structure of pure Mg, cut out the 0001 plane, construct a 4×4×6 supercell of 96 atoms, and replace one atom in the surface layer with a different solute atom (common magnesium negative electrode alloying elements Sn, Al, Li, Mn, Y, Gd are selected);
[0036] 2. Optimize the stable structure of pure magnesium doped with different solute atoms and extract the corresponding energy. In addition, based on the above doping structure, H and H 2 O molecules are placed above the solute atoms, and after structural optimization, different models are obtained to stably adsorb H and H 2 The structure and corresponding energy of O molecules.
[0037] 3. Extract the adsorption of H and H in different doping models from the output file of structure optimization 2 The energy before and after O is the difference between the two and the isolated H and H are subtracted 2 The energy corresponding to O is calculated to calculate the total energy change before and after adsorption of different doping models.
[0038] 4. Adsorption of H and H for different doping models 2 After the structure optimization of O, phonon calculation was performed to extract H and H adsorbed on the surface of different models from the output file of phonon calculation. 2 O corresponding to the vibration frequency, so as to obtain different models of adsorption of H and H 2 The zero point can change before and after O.
[0039] 5. Calculation of adsorption of H or H in different models 2 The product of the vibration entropy change of the rear surface of O and the temperature.
[0040] 6. Calculate H and H for different doping models using the Gibbs free energy formula 2 The adsorption free energy of O is given in Table 1. The adsorption Gibbs free energy of the surfaces of different doping models is given in Table 1.
[0041] Table 1: H and H after pure magnesium is doped with different atoms 2 Adsorption free energy of O
[0042]
[0043] 7. Select H or H 2 The two elements with the largest absolute value of O adsorption free energy are Mn and Sn; the composition of the magnesium negative electrode is set to: Mn 0.5wt.%, Sn 0.5wt.%, and the rest is Mg.
[0044] 8. Heat the preheated pure magnesium to 730°C, introduce protective gas at the same time, and after the magnesium is completely melted, adjust the temperature to 720°C, add the preheated Mg-10Mn master alloy and pure Sn in sequence, and keep it still for 10 minutes; 9. Stir the alloy liquid for 2 minutes to ensure that the alloy elements are evenly distributed. Then, after removing the scum on the surface of the alloy liquid, immediately pour it into a metal mold preheated at 200°C, wait for it to cool and solidify to form an alloy ingot; the obtained alloy ingot is cut and prepared into a negative plate for the test of magnesium-air battery.
[0045] Material characterization by Figure 1 It can be seen that Mn and Sn are mainly dissolved in the magnesium alloy matrix, which corresponds to the solid solution model used in theoretical calculations. Mn and Sn both show uneven distribution structural characteristics. A small amount of Sn precipitates in the form of a second phase, presenting a dendrite morphology.
[0046] Performance Testing
[0047] The alloy material in Example 1 was made into a negative electrode, and MnO was loaded 2 The commercial air electrode of / C catalyst was used as the positive electrode, the electrolyte was 3.5wt.% NaCl aqueous solution, and the test temperature was room temperature. The discharge test was carried out. The discharge voltage was tested using LAND electrical performance monitoring equipment (CT2001A). -2 and 10mA cm -2 ) for 10 hours, and the average voltage measured is taken as the discharge voltage. At the same time, the utilization efficiency is tested by discharge weight loss; the energy density is calculated by combining the discharge weight loss and discharge voltage, and the results are listed in Table 2.
[0048] Table 2: Comparison of discharge performance parameters at different current densities
[0049]
[0050] As can be seen from Table 2, the discharge performance of Example 1 is better than that of high-purity magnesium, achieving a simultaneous improvement in negative electrode efficiency and discharge voltage. This shows that the method of designing a magnesium negative electrode that simultaneously improves negative electrode efficiency and discharge voltage based on hydrogen adsorption free energy is more effective.
[0051] Depend on Figure 3It can be seen that after discharge, Example 1 dissolves more slowly during the discharge process, and the initial scratches are still visible. Mn and Sn in the solid solution and alloy can significantly increase the Gibbs free energy of the hydrogen evolution reaction, creating thermodynamically unfavorable conditions for the hydrogen evolution reaction on the magnesium surface, thereby slowing down the hydrogen evolution reaction. The inhibition of the hydrogen evolution reaction is beneficial to improving the efficiency of the negative electrode. At the same time, the cross-sectional morphology of the discharge product shows that the surface discharge product of Example 1 is easier to fall off, which is beneficial to improving local activity. Therefore, the solid solution of Mn and Sn can inhibit the overall hydrogen evolution and improve the utilization efficiency of the magnesium negative electrode. In addition, when the hydrogen evolution reaction is inhibited, it is beneficial to the negative shift of the corrosion potential, which can be Figure 3 This is proved by the potentiodynamic polarization curve in . Generally speaking, a negatively shifted potentiodynamic polarization curve is beneficial to improving the initial discharge voltage. Therefore, the easily detached discharge products and the higher initial discharge voltage are the essential reasons why Example 1 can improve the discharge activity. In summary, the alloy composition method provided by the present invention is effective, the designed alloy has excellent performance, and is a magnesium-air battery negative electrode material with excellent performance.
[0052] Although preferred implementation cases have been listed and described in detail herein, those skilled in the art will appreciate that various improvements, additions, substitutions, etc. may be made without departing from the spirit of the invention, and these contents are considered to be within the scope of the invention as defined by the claims.
Claims
1. A method for designing negative electrode components of magnesium-air batteries based on adsorption free energy, characterized in that: The following steps are involved: (1) Modeling: Using the hexagonal close-packed crystal structure of pure Mg, the 0001 plane was cut out to construct a 4×4×6 supercell of 96 atoms, in which one atom in the surface layer was replaced by a solute atom. The solute atom was another metal element doped in the magnesium alloy. A model doped with different types of solute atoms was constructed to study the effect of the solute atom type on the hydrogen evolution reaction on the magnesium surface at an equal atomic ratio, thereby screening out the appropriate solute element type; (2) Structural optimization: Based on step (1), the open source Quantum-ESPRESSO was used for density functional theory calculations, using the Perdew–Burke–Ernzerhof (PBE) exchange-correlation approximation and ultrasoft pseudopotentials with an energy cutoff of 450 eV or 769 eV. The k-point grid was set to 4 × 4 × 1 and the The vacuum layer is used to avoid the mutual influence between periodic units. The force convergence criterion for atomic structure optimization is The total energy convergence criterion is 1×10 -4 eV, and the structure was optimized to obtain the stable structures of different doping models and their corresponding energies. In addition, based on the above stable structures, H and H2O molecules were placed above the solute atoms, and the same structure optimization method was used to obtain the structures of different doping models that stably adsorb H and H2O molecules and their corresponding energies. (3) Calculation of total energy change (ΔE) before and after adsorption: After the structural optimization in step (2), the energy corresponding to the adsorption of H or H2O by different doping models before and after is extracted from the output file. The difference between the two is subtracted from the energy corresponding to the isolated H or H2O, thereby obtaining the ΔE corresponding to the different doping models. The calculation formula is as follows: △E=E 后 -AND 前 -AND 吸附 Among them, ΔE is the total energy change before and after the adsorption of H or H2O, Ebefore and Eafter are the energies corresponding to the doping model before and after the adsorption of H or H2O, E 吸附 are the energies of isolated H or H2O molecules, -1.73 eV and -14.22 eV respectively; (4) Calculation of zero-point energy change before and after adsorption (ΔZPE): After the structure is optimized in step (2), the stable structures after H or H2O adsorbed by different doping models are obtained, and phonon calculation is performed. The vibration frequencies corresponding to H or H2O adsorbed on the surface of different doping models are extracted from the output file of the phonon calculation, and the zero-point energy change is calculated by the following formula: △ZPE=1 / 2∑hν i -ZPE 吸附 Where h is Planck's constant, v i is the i-th vibration frequency corresponding to the adsorption of H or H2O on the surface of different doping models, ZPE 吸附 is the zero-point energy of isolated H or H2O, which are 0.135eV and 0.28eV respectively; (5) Calculation of the product of vibration entropy and temperature before and after adsorption (TΔS): After H or H2O is adsorbed by different doping models, the product of the vibration entropy and temperature on the surface is calculated as follows: Where T is the temperature, ΔS is the change in vibration entropy before and after adsorption, k B is the Boltzmann constant, h is the Planck constant, vi is the i-th vibration frequency corresponding to the adsorption of H or H2O on the surface of different doping models, S 吸附 is the entropy of isolated H or H2O; (6) Calculating adsorption free energy (ΔG): After obtaining ΔE, ΔZPE, and TΔS corresponding to different doping models in steps (3) to (5), the adsorption free energy of H or H2O on the surface of different doping models is calculated using the following formula: △G=△E+△ZPE-T△S Where ΔG is the adsorption free energy of H or H2O on the surface, ΔE is the total energy change before and after the adsorption of H or H2O on the surface, ΔZPE is the change in zero-point energy before and after the adsorption of H or H2O on the surface, and TΔS is the product of the entropy change before and after the adsorption of H or H2O on the surface and the temperature, where T is generally set to 300K. (7) Composition design: The larger the absolute value of either H or H2O adsorption free energy, the more favorable it is to inhibit hydrogen evolution, thereby improving the utilization efficiency and initial discharge voltage of the magnesium alloy negative electrode; calculate the adsorption free energy of H and H2O on the surface of different doping models, compare and contrast the absolute values, and screen out two doping solute elements. The models corresponding to these two doping solute elements have relatively high absolute values of H or H2O adsorption free energy. The two doping solute elements selected out together with pure magnesium form a ternary magnesium alloy.
2. The method according to claim 1, characterized in that After the doping solute elements are determined in step (7), the addition amount of the two solute elements is about 0.5 wt.%, and the rest is pure magnesium.
3. The method according to claim 1 or 2, characterized in that The alloy is prepared according to the obtained composition. Pure magnesium is preheated and melted in a resistance furnace. After the magnesium is completely melted, the preheated pure metals or intermediate alloys corresponding to the other two elements are added at the same time. Ventilation protection (SF6+N2, gas volume ratio 1:19) is provided during the heating process. After the temperature of the alloy melt reaches 720°C, it is poured into a metal mold to obtain an ingot.